Elastisitas Pajak Kendaraan Bermotor di Sumatera Selatan - Didik Susetyo (Program Studi Magister Manajemen FE Unsri, 2009)
The objective of this research is to identify the influence of gross regional domestic product (GRDP), the number of population, and the number of vehicles to the received of vehicle taxes and fees in the South Sumatra. The scope of this research was focused on the elasticity of two vehicles taxes and fees. The secondary data of period 1991-2007 was used. The qualitative and quantitative description approaches and multiple regression analysis were applied. The results of this research showed that: (1) the simultaneous influence of gross regional domestic product (GRDP), the number of population, and the number of vehicles to the receipt of the vehicles taxes and fees was statistically siqnificant. The coefficient of determination R2 = 97,8% showed that increasing of the GRDP, the number of population, and the number of vehicles explained the increasing of the vehicles taxes and fees in South Sumatra, and the residual 2,2% explained by other factors. (2) The elasticity of GRDP, the number of population, and the number of vehicles to the revenues of the vehicles taxes and fees was in-elastic. It meaned that the change of the vehichel taxes and fees was less responsive to the change of the GRDP, number of population, and number of vehichel in South Sumatra.Keywords: Vehicle taxes and fees, number of vehicles, GRDP, number of population, elasticity